2019
DOI: 10.3389/fpsyg.2019.00637
|View full text |Cite
|
Sign up to set email alerts
|

Recovery After Genocide: Understanding the Dimensions of Recovery Capital Among Incarcerated Genocide Perpetrators in Rwanda

Abstract: Utilizing survey data from 302 men and women incarcerated in the Rwandan correctional system for the crime of genocide, and structured interviews with 75 prisoners, this mixed methods study draws on the concept of recovery capital to understand how individuals convicted of genocide navigate post-genocide healing. Genocide smashes physical and human capital and perverts social and cultural capital. Experiencing high levels of posttraumatic stress symptoms with more than two-thirds of the sample scoring above ty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 79 publications
0
4
0
Order By: Relevance
“…Our results revealed that youth born to both genocide survivors and perpetrators experienced negative psychological effects. Among youth descended from genocide perpetrators, some whose parents were prisoners or ex-prisoners experienced psychological and social problems, including depression, trauma, anxiety disorders, thoughts of revenge, anti-social behaviors, frustration, shame, guilt, phobias [ 54 ], dropping out of school [ 55 ], loss of trust, loss of safety, poor parental affection, drug abuse, breaking laws and weakness to attend some of the policies or communities organized by the local, sexual reproductive health problems (such as unwanted pregnancies), problems in marital relationships, and domestic violence [ 56 ]. We found that without treatment, the severity of the symptoms increased, becoming even more acute for the children of genocide perpetrators.…”
Section: Discussionmentioning
confidence: 99%
“…Our results revealed that youth born to both genocide survivors and perpetrators experienced negative psychological effects. Among youth descended from genocide perpetrators, some whose parents were prisoners or ex-prisoners experienced psychological and social problems, including depression, trauma, anxiety disorders, thoughts of revenge, anti-social behaviors, frustration, shame, guilt, phobias [ 54 ], dropping out of school [ 55 ], loss of trust, loss of safety, poor parental affection, drug abuse, breaking laws and weakness to attend some of the policies or communities organized by the local, sexual reproductive health problems (such as unwanted pregnancies), problems in marital relationships, and domestic violence [ 56 ]. We found that without treatment, the severity of the symptoms increased, becoming even more acute for the children of genocide perpetrators.…”
Section: Discussionmentioning
confidence: 99%
“…Some churches have been transformed in site of memorial, and in front of others are built memorial sites. Barnes-Ceeney, et al, (2019), in their study on recovery after genocide, found that genocide against the Tutsi impacted victims, eyewitnesses, perpetrators, and those entering Rwanda post-genocide for nation reconstruction. The aim of this study was to examine the key components of recovery capital, social capital, cultural capital, physical capital, and human capital.…”
Section: Study Carried Out Bymentioning
confidence: 99%
“…Statistics of 2004, estimate that 3.4% of the Rwandan prison population was comprised of female genocide perpetrators at that time, approximately 3000 women. 11 Prior studies conducted on the participation of women in the genocide in Rwanda confirmed that genocide crimes are mostly committed by men, especially when it comes to the actual physical acts of violence, rape and killings. The same studies found that women are considered to be more "gender-consonant" and include mainly looting or denouncement.…”
Section: The Experience Of Abandonmentmentioning
confidence: 99%
“…In mid-1998, at the height of arrests, approximately 130,000 people were incarcerated in prisons and communal lockups, most of them charged with genocide or related crimes. [9][10][11] By collecting and analyzing the life stories of eight prisoners incarcerated for genocide crimes, this study tries to unravel the personal meaning making process of this particular group. The meaning making process includes how they construe, understand or make sense of their life experiences, their relationships and of their sense-of-self.…”
Section: Introductionmentioning
confidence: 99%